District Administrator Perspectives on Student Learning in an Era of Standards and Accountability: A Collective Frame Analysis - Anderson, Stephen; Macri, Joelle (Canadian Journal of Education/Revue canadienne de l’éducation, 2009)
Our analysis explores the agenda for student learning communicated in interviews with school district officials from four Ontario districts. Using research methods drawn from collective action framing theory, we identified six core frames and one broader frame in the discourse on student learning: (a) measureable academic achievement, (b) personalized preparation for post‐secondary destinations, (c) a well‐rounded education, (d) personal development, (e) faith/values‐based education, (f) social identity development, and (g) developing the whole child (the broader frame). The analysis highlights the administrators’ advocacy for a more encompassing educa‐ tional agenda than that mandated by government curriculum and accountability policies, and the utility of framing theory for education policy analysis. Key words: school district administrators, accountability, learning, policy analysis, curriculum analysis Les auteurs analysent les priorités des administrateurs de commissions scolaires quant à l’apprentissage des élèves telles qu’elles ressortent des entrevues menées dans quatre commis‐ sions scolaires en Ontario. À l’aide de méthodes de recherche tirées de la théorie du cadrage de l’action collective, les auteurs ont identifié six cadres clés et un cadre plus vaste dans le discours des administrateurs de commissions scolaires sur l’apprentissage des élèves : (a) le rendement scolaire mesurable, (b) la préparation personnalisée pour le postsecondaire, (c) une éducation complète, (d) le développement personnel, (e) une éducation reposant sur la foi/des valeurs, (f) le développement de l’identité personnelle et (g) le développement de l’enfant dans toutes ses di‐ mensions (le cadre plus vaste). L’analyse met en lumière le combat des administrateurs pour une orientation plus englobante que celle que prescrit le gouvernement dans les curriculums et les politiques en matière d’imputabilité ainsi que l’utilité de la théorie du cadrage dans l’étude des politiques en matière d’éducation. Mots clés : administrateurs d’arrondissement scolaire, imputabilité, apprentissage, analyse de politiques, analyse d’un curriculum.